Памяти выдающегося украинского ученого и педагога, профессора Заблонского Константина Ивановича - Гутыря, С. С.; Мотулько, Б. В.; Яглинский, Виктор Петрович; Моргун, Б. А.; Хихловский, А. Б. (НТУ "ХПИ", 2015)
Представлен биографический очерк о жизненном и фронтовом пути, учебе и трудовых достижениях известного украинского ученого, педагога, многолетнего руководителя известной в научном мире Одесской школы механики и деталей машин, ректора Одесского политехнического института (1969-1985г.г.), профессора К. И. Заблонского, написанный его учениками и сотрудниками в связи со 100-летием со дня рождения Учителя. Жизненный путь проф. Заблонского является замечательным примером непрерывной учебы, настойчивого поиска научных знаний, честного самоотверженного труда в интересах Родины, порученного дела, института и кафедры, коллег и учеников, семьи и друзей.

The biographic sketch about a vital and front way, study and labor achievements of the famous Ukrainian scientist, teacher, long-term head of the well known in the scientific world Odessa’s school of mechanics and details of machines, the rector of the Odessa polytechnic institute (1969-1985), the prof. K. I. Zablonsky, written by his pupils and colleagues, to the 100 anniversary since the birth of the Teacher, is presented. Professor Zablonsky is the author of known scientific works in the field of rigidity, loadability and improvement of designs of gearings, and also textbooks on such basic engineering and mechanical disciplines as "The Theory of mechanisms and machines", "Machines elements ", "Applied mechanics", "Bases of design of machines", "Design of units and mechanisms of devices". Professor Zablonsky – the author of 430 scientific works, including 11 monographs and 25 inventions. As the research supervisor and the consultant prepared 48 Doctors of Engineering and 5 Doctors of Science. The course of life of the professor K. I. Zablonsky is a remarkable example of continuous study, persistent search of scientific knowledge, honest dedicated work in interests of the Homeland, the charged work, institute and chair, colleagues and pupils, a family and friends.
Memories of the outstanding Ukrainian scientist and teacher professor Zablonsky Konstantin Ivanovich
Keywords: детали машин; передача зацеплением; проектирование; очерк биографический; ученый; профессор; педагог; ректор; Одесский политехнический институт; machines elements; gear; design; biographic sketch